Prevalence and correlates of depression and anxiety among patients with HIV on-follow up at Alert Hospital, Addis Ababa, Ethiopia. Issue 1 (December 2016) - Tesfaw, Getachew; Ayano, Getinet; Awoke, Tadesse; Assefa, Dawit; Birhanu, Zelalem; Miheretie, Getenet; Abebe, Genet
Abstract Background Depression and anxiety disorders are common among people living with Human Immunodeficiency Virus than the non-infected individuals. The co-existence of these disorders are associated with barriers to treatment and worsening medical outcomes, including treatment resistance, increased risk for suicide, greater chance for recurrence and utilization of medical resources and/or increase morbidity and mortality. Therefore, assessing depression and anxiety among HIV patients has a pivotal role for further interventions. Methods Institution based cross-sectional study was conducted at ALERT hospital May, 2015. Data were collected using a pretested, structured and standardized questionnaire. Systematic sampling technique was used to select the study participants. Binary logistic regression analysis was used to identify associated factors. Odds ratio with 95 % CI was computed to assess the strength of associations. Results The prevalence of co-morbid depression and anxiety among HIV patients was 24.5 % and prevalence of depression and anxiety among HIV patients was 41.2 % (172) and 32.4 % (135) respectively. Multivariate analysis showed that individual who had perceived HIV stigma (AOR = 3.60, 95 % CI (2.23, 5.80), poor social support (AOR = 2.02, 95 % CI (1.25, 3.27), HIV stage III (AOR = 2.80, 95 % CI (1.50, 5.21) and poor medication adherence (AOR = 1.61, 95 % CI (1.02, 2.55) were significantly associated with depression. Being female (AOR = 3.13, 95 % CI (1.80, 5.44), being divorced (AOR = 2.51, 95 % CI (1.26, 5.00), having co morbid TB (AOR = 2.74, 95 % CI (1.37, 5.47) and perceived HIV stigma (AOR = 4.00, 95 % CI (2.40, 6.69) were also significantly associated with anxiety. Conclusion Prevalence of depression and anxiety was high. Having perceived HIV stigma, HIV Stage III, poor social support and poor medication adherence were associated with depression. Whereas being female, being divorced and having co morbid TB and perceived HIV stigma were associated with anxiety. Ministry of health should give training on how to screen anxiety and depression among HIV patients and should develop guidelines to screen and treat depression and anxiety among HIV patients.